Docu(women)tary a textual analysis of the similarities and differences in the representation of women in poverty in I-Witness and Kodao documentaries - Miguel, Jade Dela Cruz (2013)
"This study aims to determine how documentaries represent women in poverty. The researcher analyzed the images shown in I-Witness and Kodao Productions by using textual analysis. I-Witness and Kodao are chosen to determine the similarities and differences of mainstream (I-Witness) and alternative media (Kodao) in their women representation. Feminism serves as a framework of this study. Cultural feminism is used to analyze I-Witness episodes whereas Marxist feminism on Kodao. The researcher's assumption is that these frameworks might have been embedded in images and language shown in the corresponding documentaries. The researcher has gained interest to examine women under conditions of poverty since it has been a pervading theme in Philippine documentaries. Featuring the lack of basic needs and services being suffered by people belonging to the lower class, these documentaries have continuously shaped and re-shaped the public perception of poverty through the images represented in every episode. As part of the audience, she has observed that women have always been presented as case studies particularly on issues about equality, women's rights, reproductive health, labor force, and other societal issues. Thus, this has prompted her to work in a study which examines the representation of women in poverty. The study has analyzed that women are indeed suffering in absolute poverty. Women lack freedom due to deprivation of basic needs and services. It has been examined that there are certain behaviours and traits of women which characterized the persistence of poverty. However, it has also been analyzed that there have been attempts to resist not only the traditional roles ascribed to women but also the oppressive patriarchal system itself which subordinates women."